2020
DOI: 10.3390/molecules25092073
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Nanomaterial Based on Single Walled Carbon Nanotubes Cross-Linked via Axially Substituted Silicon (IV) Phthalocyanine for Chemiresistive Sensors

Abstract: In this work, the novel hybrid nanomaterial SWCNT/SiPc made of single walled carbon nanotubes (SWCNT) cross-linked via axially substituted silicon (IV) phthalocyanine (SiPc) was studied as the active layer of chemiresistive layers for the detection of ammonia and hydrogen. SWCNT/SiPc is the first example of a carbon-based nanomaterial in which an axially substituted phthalocyanine derivative is used as a linker. The prepared hybrid material was characterized by spectroscopic methods, thermogravimetry, scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Carbon nanomaterials, such as single-walled carbon nanotubes (SWCNTs), pristine carbon nanomaterials, multi-walled carbon nanotubes (MWCNTs), and graphene, have been extensively used as the active layers for the development of chemoresistive sensors [ 5 , 6 , 7 ]. This shift in material usage has been motivated by Kong et al, who observed a change in the conductivity of carbon nanotube (CNT) functionalized materials on gas absorption, leading to their use in a range of gas sensors [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanomaterials, such as single-walled carbon nanotubes (SWCNTs), pristine carbon nanomaterials, multi-walled carbon nanotubes (MWCNTs), and graphene, have been extensively used as the active layers for the development of chemoresistive sensors [ 5 , 6 , 7 ]. This shift in material usage has been motivated by Kong et al, who observed a change in the conductivity of carbon nanotube (CNT) functionalized materials on gas absorption, leading to their use in a range of gas sensors [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functionalization of SWCNTs with phthalocyanines made it possible to significantly improve sensing characteristics by means of the covalent or non-covalent functionalization of carbon nanotubes [108]. The cross-sensitivity data presented in [124] showing the significantly higher sensitivity of SWCNT/substituted silicon (IV) phthalocyanine sensors to volatile organic compounds (VOCs) and CO2 make them attractive for the analysis of exhaled breath. In [107], it was found that SWCNTs covalently function-…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%
“…The functionalization of SWCNTs with phthalocyanines made it possible to significantly improve sensing characteristics by means of the covalent or non-covalent functionalization of carbon nanotubes [ 108 ]. The cross-sensitivity data presented in [ 124 ] showing the significantly higher sensitivity of SWCNT/substituted silicon (IV) phthalocyanine sensors to volatile organic compounds (VOCs) and CO 2 make them attractive for the analysis of exhaled breath. In [ 107 ], it was found that SWCNTs covalently functionalized with 1-[N-(2-ethoxyethyl)-4-pentynamide]-8(11),15(18),22(25)-tris-{2-[2-(2-ethoxyethoxy)ethoxy]-1-[2-((2-ethoxy ethoxy)-eth-oxy)methyl]ethyloxy}zinc(II) phthalocyanine (ZnPc) possessed higher responsiveness that non-covalently functionalized SWCNTs, which was in correlation with the number of ZnPc molecules adsorbed.…”
Section: Gas Sensors Based On Carbon Nanotubesmentioning
confidence: 99%
“…In a series of our research group, 3D hybrid materials based on SWCNTs and various polyaromatic linking molecules, viz. pyrene, [74] coumarin, [75,76] BODIPY, [77] and silicon phthalocyanine, [78] were prepared and studied. The hybrids were synthesized according to the well-known reaction of "click chemistry", namely azide-alkyne Huisgen cycloaddition (Figure 9).…”
Section: D Materials Based On Carbon Nanotubesmentioning
confidence: 99%